PEMANFAATAN SERABUT KELAPA SEBAGAI BIOSORBEN DALAM REMOVAL COD PADA LIMBAH CAIR INDUSTRI PEWARNA MAKANAN - Dian Yanuarita Purwaningsih; Eka Cahya Muliawati (Journal of Industrial Process and Chemical Engineering (JOICHE), 2022)
The liquid waste of the food industry has recently increased. Therefore, when it is discharged into the waters, it will cause turbidity and can damage the ecosystem inside. One of the wastewater treatment techniques is absorption using biosorbents, one of which is made from coconut fiber to reduce the color intensity of the liquid waste. The purpose of this study was to determine the effects of the coconut fiber biosorbent on the color intensity, COD, and pH of the liquid waste of the food industry. In this research, the coconut fiber was delignified with a 2 M NaOH solution and then activated with a 3 N solution. The research variables consisted of the weight percentages of biosorbent by 1%, 2%, 3%, 4%, and 5%, and the contact time of 30 and 60 minutes with shaker stirring. Meanwhile, the most optimum results in COD removal happened at the addition of 4% for 60 minutes, from the initial COD of 1179 mg/L O2 to 780 mg/L O2 within the removal of 26.5%. The highest pH removal of 6.98 occurred in the variable addition of 1% for 30 minutes, whereas the lowest pH removal of 6.5